Glucose-Assisted Synthesis of Nickel-Cobalt Sulfide/Carbon Nanotube Composites as Efficient Cathode Materials for Hybrid Supercapacitors. Issue 8 (14th May 2015) - Lin, Tsung-Wu; Hsiao, Min-Chien; Chou, Shu-Wei; Shen, Hsin-Hui; Lin, Jeng-Yu
Abstract : In this work, nickel and cobalt binary sulfide nanoparticles are successfully decorated on the surface of multi-walled carbon nanotubes to form a composite (Ni-CoS/MWCNT) via a facile glucose-assisted hydrothermal method. By introducing the conductive MWCNT and tuning the Ni/Co molar ratio for the Ni-CoS/MWCNT composites, the optimized one shows a high capacity up to 153 mAh g −1, superior rate capability and excellent electrochemical stability. On this basis, advanced hybrid supercapacitor (HSC) is assembled by using the Ni-CoS/MWCNT composite as the cathode and reduced graphene oxide as the anode. As-fabricated HCS is able to be operated reversibly in a full voltage region of 0–1.6 V and achieves a high specific capacity of 33 mAh g −1 at 1 A g −1, therefore delivering a maximum energy density of 23 Wh kg −1 at a power density of 684 W kg −1 . Furthermore, the HSC still retains 90% of its initial discharge capacity after 2000-cycle consecutive charge/discharge test at 4 A g −1 .